Why do migrants stay unexpectedly? Misperceptions and implications for integration - Marc Kaufmann; Joël Machado; Bertrand Verheyden (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
Empirical evidence suggests that the majority of immigrants who initially planned a temporary stay end up staying permanently in the host country. Since beliefs about the duration of stay are a strong determinant of integration, many long-term migrants may end up less than optimally integrated. We theoretically model migrants with potential misperceptions about their future utility and wage prospects in the host country relative to their country of origin. We describe conditions under which these misperceptions generate, and conditions on observables that identify, unexpected staying. These conditions involve pessimism about the endogenous long-term wage for which migrants are indifferent between staying and leaving: either they overestimate the probability of earning less than this indifference wage, or they underestimate their utility in the destination country when earning this wage. Using the German Socio-Economic Panel (SOEP), we find that higher levels of pessimism about utility and wages at arrival are associated with staying in the long-term in Germany despite having initially predicted a temporary stay.
Keywords: F22; D91; J61; 330; Migrant integration; return intentions; unexpected staying; misperceptions; pessimism; SOEP